The Act of Killing: Investigative strategies for a ‘Post-Political’ Age - Alex Edney-Browne (Asia Pacific Network, 2015)
Unusually for a political documentary, The Act of Killing provides its audiences with little information, no overarching argument, nor a call-to-action. Instead, director Joshua Oppenheimer uses two unconventional investigative strategies—reenactment and an examination of media affect—to uncover the 1965 Indonesian genocide and the shadow it casts over present-day Indonesia. Although these techniques have been used previously in documentary cinema, Oppenheimer employs them in innovative ways to dig under Indonesia’s social unconscious and expose the artifice of the ‘official’ history of the genocide. This article provides a close analyses of The Act of Killing’s use of these strategies. It argues that they are not only integral to the documentary’s political success in the Indonesian context, but can also be used by political documentarists and committed journalists to mobilise otherwise disengaged audiences in our ‘non-ideological’ and ‘post-political’ age.